A high-strength, corrosion-resistant dual-phase medium-entropy alloy and a preparation method thereof
By designing high-strength corrosion-resistant biphasic mid-entropy alloys and using specific chemical composition and heat treatment processes, the problems that traditional metal materials are difficult to take into account in terms of strength and corrosion resistance are achieved, and the effects of high strength, high plasticity and excellent corrosion resistance are achieved.
Patent Information
- Application Number
- CN202410837620.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-06-26
AI Technical Summary
Traditional metal materials are difficult to take into account both strength and corrosion resistance, especially in long-term high loads and harsh environments, the performance of the materials is difficult to maintain.
By designing a high-strength corrosion-resistant biphasic medium-entropy alloy, the ratio of L12 phase and FCC phase in the alloy is regulated by using chemical components of Co: 27%-31%, Cr: 28%-32%, Ni: 27%-28%, Al: 1%-2.5%, Ti: 2%-4.5%, Cu: 5%-8%, Nb: 1%-1.5%, and a specific heat treatment process, including solid solution treatment at 1150°C and aging treatment at 700-780°C.
It realizes the high strength, high plasticity and excellent corrosion resistance of the alloy, with a pitting equivalent of more than 30, and its comprehensive performance is better than that of traditional 304 stainless steel. It is suitable for application fields that have high requirements for material strength, plasticity and corrosion resistance.
Smart Images

Figure CN118756024B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, in particular to the design and preparation of new metal materials, and specifically to a high-strength, corrosion-resistant dual-phase medium-entropy alloy and a preparation method thereof. Background Art
[0002] In the application field of engineering materials, corrosion has always been a serious problem. According to relevant data, China's economic losses caused by corrosion each year account for about 3% to 5% of its GDP. This astonishing figure highlights the urgency of improving the corrosion resistance of materials. Traditional structural materials based on one main element often seem powerless when faced with the challenge of simultaneously improving corrosion resistance and mechanical properties. It is difficult for such materials to maintain their performance under long-term high loads and harsh environments. With the continuous advancement of science and technology, the emergence of multi-main element alloys has brought new hope to the field of materials science. Such alloys break the traditional design concept of a single main element and greatly broaden the composition selection and performance range of alloy design. In particular, medium-entropy alloys and high-entropy alloys with a face-centered cubic (FCC) lattice structure have attracted much attention due to their outstanding strength, ductility and corrosion resistance.
[0003] In the strengthening method of high-entropy / medium-entropy alloys, the formation of a large number of secondary phase particles (such as "FCC+B2" and "FCC+L12" structures) is an important strategy; however, the matrix of these alloys usually has a higher stability, and the potential of most strengthening phases is more negative than that of the matrix; in this case, these secondary phase particles acting as anodes will accelerate dissolution due to the microgalvanic effect, which not only damages the corrosion resistance of the material, but also reduces its mechanical properties; therefore, when designing such alloys, in addition to considering the effective strengthening effect of the strengthening phase, it is also necessary to pay attention to the potential difference between them and the matrix to prevent the occurrence of corrosion problems.
[0004] In recent years, researchers have found that stacking faults (SFs) and long-period stacking ordered (LPSO) structures have a significant effect on improving the mechanical properties of alloys; the long-period stacking ordered structure was first observed in Au-Mn alloys and usually appears in the HCP phase, especially in rare earth magnesium alloys, where this structure exhibits varying degrees of reinforcement and toughening effects; in magnesium alloys, more stacking faults and fewer long-period stacking ordered structures can be achieved by optimizing the treatment process, thereby enhancing the protective effect of the passivation film on the surface of the magnesium alloy; in high-entropy / medium-entropy alloys, the long-period stacking ordered structure phase often appears in certain solute-rich intermetallic compounds; however, there are currently limited reports on the effects of SFs and LPSO on corrosion properties.
[0005] The corrosion resistance of an alloy depends largely on the oxide film formed on its surface; this oxide film is mainly composed of oxides of Al, Cr and Ni, and it will spontaneously cover the surface of the alloy in the presence of oxygen and / or water; the multi-element characteristics of high-entropy / medium-entropy alloys provide them with a variety of passivation elements, which help to improve corrosion resistance; currently, although high-entropy / medium-entropy alloys containing precipitated phases have attracted widespread attention due to their excellent mechanical properties, it is often difficult to strike a balance between improving the corrosion resistance of such alloys and strengthening the precipitated phases.
[0006] In summary, based on the existing research results of medium-entropy alloys, further optimizing their composition, developing and designing duplex medium-entropy alloys with high strength, high plasticity and excellent corrosion resistance are of extremely important significance and engineering application value for enriching and improving the varieties and performance of existing stainless steels; the present invention came into being in this context, aiming to solve the above-mentioned technical problems and promote the progress of metal material technology. Summary of the invention
[0007] In view of the problem that existing metal materials are difficult to balance in terms of strength and corrosion resistance, the present invention proposes a composition design and a preparation method of a high-strength and corrosion-resistant two-phase medium-entropy alloy. Through carefully designed alloy composition and specific heat treatment process, the present invention successfully develops a two-phase medium-entropy alloy with both high strength and high corrosion resistance, providing a new solution for the field of metal materials.
[0008] The technical solution adopted by the present invention is: a high-strength, corrosion-resistant dual-phase medium-entropy alloy, the alloy is composed of the following elements in mass percentage: Co: 27%-31%, Cr: 28%-32%, Ni: 27%-28%, Al: 1%-2.5%, Ti: 2%-4.5%, Cu: 5%-8%, Nb: 1%-1.5%, B<0.01%, Mg<0.02%, and the rest are inevitable impurities; wherein the pitting corrosion resistance equivalent of the alloy is greater than 30.
[0009] A preparation method of a high-strength, corrosion-resistant dual-phase medium-entropy alloy comprises the following steps: preparing each element according to a set mass percentage, smelting in a vacuum arc furnace to obtain an alloy melt, and then subjecting the alloy melt to a specific heat treatment, wherein the specific heat treatment comprises a solution treatment at 1150°C for 12 to 24 hours, followed by an aging treatment at a temperature range of 700 to 780°C for 1 to 50 hours, and finally water cooling to room temperature to obtain an alloy.
[0010] After the alloy is subjected to specific heat treatment, the content ratio of the L12 phase to the FCC phase in the structure reaches 1:2.
[0011] The alloy has a yield strength greater than 1 GPa, a tensile strength greater than 1.4 GPa, and an elongation greater than 15%.
[0012] During a specific heat treatment process, the ratio of L12 phase to FCC phase in the alloy structure is regulated to be close to 1:2 to achieve a good match between strength and toughness.
[0013] The heat treatment can be carried out in a common box furnace or a vacuum heat treatment furnace.
[0014] The alloy has excellent corrosion resistance in NaCl solution, and the corrosion current density is less than 2×10 -7 A / cm 2 .
[0015] The alloy has better comprehensive properties than traditional 304 stainless steel and is suitable for application fields with high requirements on material strength, plasticity and corrosion resistance.
[0016] The beneficial effects of the present invention are mainly reflected in the following aspects: in terms of alloy composition design, the present invention is based on the CoCrNi medium entropy alloy with excellent mechanical properties, and forms a new alloy system by adding low-content Al, Ti, Cu, Nb elements and trace amounts of B and Mg grain boundary strengthening elements; these added elements play a key role in the alloy, among which the addition of Al, Ti, Cu, and Nb elements helps to form the second phase - L12 phase, while trace amounts of B and Mg elements strengthen the grain boundaries and improve the overall performance of the alloy.
[0017] In terms of preparation process, the present invention adopts a specific heat treatment process to regulate the microstructure of the alloy; by performing solid solution treatment at 1150°C for 12 to 24 hours, then performing aging treatment at a temperature range of 700-780°C for 1 to 50 hours, and finally water cooling to room temperature; this heat treatment process can accurately regulate the ratio of L12 hard phase and FCC soft phase in the alloy to make it close to 1:2, thereby achieving a good match between the strength and toughness of the alloy.
[0018] Through precise configuration of alloy components and optimization of heat treatment process, a large number of stacking faults and long-period stacking ordered structures appear in the alloy of the present invention, which help to improve the corrosion resistance of the alloy; at the same time, the alloy has an anti-pitting equivalent of greater than 30, showing excellent pitting resistance.
[0019] The high-strength and corrosion-resistant dual-phase medium-entropy alloy of the present invention has high strength, high plasticity and excellent corrosion resistance, and its comprehensive performance is better than most of the precipitation-strengthened high-entropy alloys and medium-entropy alloys reported so far; this alloy can be widely used in application fields with high requirements on material strength, plasticity and corrosion resistance, such as aerospace, petrochemical, marine engineering, etc.
[0020] The innovation of the present invention is that the problem of the difficulty in achieving both strength and corrosion resistance of traditional metal materials is successfully solved through the carefully designed alloy composition and specific heat treatment process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is the X-ray diffraction pattern of the high-strength and corrosion-resistant dual-phase medium-entropy alloy in the embodiment after aging treatment at 700℃ / 4h, 750℃ / 4h and 750℃ / 10h.
[0022] Figure 2 (a), (b), and (c) are the microstructures of the L12 phase of the high-strength and corrosion-resistant dual-phase medium-entropy alloy in the embodiment after aging treatment at 700℃ / 4h, 750℃ / 4h, and 750℃ / 10h, respectively.
[0023] Figure 3 : The stress-strain curves of the high-strength, corrosion-resistant dual-phase medium-entropy alloy in the embodiment after aging treatment at 700°C / 4h, 750°C / 4h, and 750°C / 10h.
[0024] Figure 4 The precipitated phase, dislocation and stacking fault in the TEM structure of the high-strength and corrosion-resistant dual-phase medium entropy alloy in the embodiment.
[0025] Figure 5 These are the polarization curves of the high-strength, corrosion-resistant dual-phase medium-entropy alloy in the embodiment after aging treatment at 700°C / 4h, 750°C / 4h, and 750°C / 10h in NaCl solution.
[0026] Figure 6 This is the surface morphology of the high-strength and corrosion-resistant dual-phase medium-entropy alloy in the embodiment after aging treatment at 700℃ / 4h, 750℃ / 4h, and 750℃ / 10h and electrochemical corrosion in NaCl solution. DETAILED DESCRIPTION
[0027] The specific implementation of the present invention is described in detail below with reference to the accompanying drawings:
[0028] like Figure 1-6 As shown, a high-strength corrosion-resistant dual-phase medium-entropy alloy composition design and preparation method thereof, characterized in that the chemical composition and mass percentage of the alloy composition alloy are: Co: 27%-31%, Cr: 28%-32%, Ni: 27%-28%, Al: 1%-2.5%, Ti: 2%-4.5%, Cu: 5%-8%, Nb: 1%-1.5%, B<0.01%, Mg<0.02%; the pitting corrosion equivalent of the steel plate is greater than 30, and the pitting corrosion equivalent PREN=%Cr+(3.3×%Mo)+(30×%N), specifically as follows:
[0029] Table 1 shows the mass percentage of each component.
[0030]
[0031] The ingredients were prepared according to the ingredients in Table 1. A total of 50 g of single substances Co, Cr, Ni, Al, Ti, Cu, and Ni with a purity greater than 99.9% were weighed using an electronic balance with an induction capacity of 0.1 mg. The single substances were washed and dried with alcohol and placed in the furnace chamber of a vacuum arc melting furnace. The vacuum was evacuated to a degree of less than 5 × 10 -3 Pa, and filled with 99.9% pure argon protection, so that the pressure in the furnace is -0.5MPa relative to the standard atmospheric pressure; then turned over and repeated smelting 2 to 3 times, introduced magnetic stirring during the smelting process and smelted 2 to 3 times, finally, cooled to room temperature in a copper crucible to obtain a cast alloy, and the cast alloy was solution treated at 1150°C for 12h, and then aging treatments were performed at 700°C / 4h, 750°C / 4h and 750°C / 10h, respectively, and then quickly water-cooled to room temperature.
[0032] Figure 1 The X-ray diffraction patterns of the high-strength and corrosion-resistant dual-phase medium-entropy alloy after aging treatment at 700℃ / 4h, 750℃ / 4h, and 750℃ / 10h show that the alloy structure always contains only FCC phase and L12 phase. Figure 2 This corresponds to the microstructure of the L12 phase after aging treatment. As the temperature increases, the size of the precipitated phase increases. The L12 phase content after aging at 750℃ / 4h is the largest, close to 1:2. Figure 3 The tensile results of the medium-high strength corrosion-resistant dual-phase medium entropy alloy after aging treatment at 700℃ / 4h, 750℃ / 4h, and 750℃ / 10h; the corresponding mechanical properties are shown in Table 2:
[0033] Table 2 shows the mechanical properties corresponding to the main process parameters
[0034]
[0035]
[0036] Figure 4 Precipitation phase, dislocation and stacking fault in TEM structure of high strength and corrosion resistant dual phase medium entropy alloy after aging treatment at 750℃ / 4h; Figure 4 There are a large number of dislocation lines around the dark L12 phase in (a), accompanied by twins. Figure 4 (b) The stacking faults in the FCC matrix intersect with each other to form dislocation pinning points; therefore, the high-strength, corrosion-resistant duplex medium-entropy stainless steel of the present invention can achieve good strength-toughness matching through this mechanism.
[0037] Figure 5 and Figure 6Polarization curves of high-strength and corrosion-resistant dual-phase medium-entropy alloys in NaCl solution and surface morphologies after electrochemical corrosion. All three alloys after different aging conditions show excellent corrosion resistance. Figure 5 There is a secondary passivation interval in all of them, and the corresponding electrochemical corrosion data are shown in Table 3; Figure 6 There was no obvious corrosion phenomenon and no pitting pits on the surfaces of the three alloys.
[0038] Table 3 shows the corresponding electrochemical corrosion data
[0039]
[0040] Example 1: Preparation of high-strength and corrosion-resistant dual-phase medium-entropy alloy and performance testing thereof
[0041] This example describes in detail the preparation process of a high-strength, corrosion-resistant dual-phase medium-entropy alloy, and tests its mechanical properties.
[0042] The ingredients are prepared according to the chemical composition and mass percentage in the technical solution. The specific composition is shown in Table 1. High-purity single elements are used for smelting. The atmosphere and temperature are strictly controlled during the smelting process to ensure the purity and uniformity of the alloy.
[0043] The cast alloy was solution treated at 1150°C for 12 hours, then aged at 700°C for 4 hours, and then rapidly cooled to room temperature by water. X-ray diffraction analysis was performed on the prepared alloy to confirm that the alloy structure contained only FCC phase and L12 phase.
[0044] The alloy was subjected to tensile testing, and the results showed that the alloy had a yield strength of 1152.9 MPa, a tensile strength of 1446.5 MPa, and an elongation of 15.1%. This result proves that the alloy has excellent mechanical properties, especially high strength and good ductility. Example 2: Effect of Optimizing Aging Treatment on the Properties of High-Strength and Corrosion-Resistant Dual-Phase Medium-Entropy Alloy
[0045] This example discusses the effects of different aging treatment conditions on the properties of a high-strength, corrosion-resistant dual-phase medium-entropy alloy.
[0046] On the basis of Example 1, the cast alloy was subjected to the same solution treatment and then to aging treatment at 750°C / 4 hours and 750°C / 10 hours, respectively; through X-ray diffraction analysis and microstructure observation, it was found that with the increase of aging temperature, the size of the L12 phase increased, and after aging at 750°C / 4 hours, the content of the L12 phase reached the maximum, approaching a ratio of 1:2.
[0047] Tensile tests were carried out on the two alloys after aging treatment. The results showed that the alloy aged at 750℃ / 4 hours had a yield strength of 1188.3MPa, a tensile strength of 1529.0MPa, and an elongation of 16.9%; while the alloy aged at 750℃ / 10 hours had a yield strength of 1048.5MPa, a tensile strength of 1407.6MPa, and an elongation of 22.9%. These data indicate that by optimizing the aging treatment conditions, the mechanical properties of the alloy can be further controlled to meet the needs of different application scenarios.
[0048] Example 3: Corrosion performance test of high strength and corrosion resistant dual phase medium entropy alloy
[0049] In this example, the corrosion performance of a high-strength and corrosion-resistant dual-phase medium-entropy alloy in a NaCl solution was tested.
[0050] The alloy samples prepared in Example 1 and Example 2 were selected to carry out polarization curve test and electrochemical corrosion experiment in NaCl solution; the results showed that the alloys after three different aging treatments all showed excellent corrosion resistance, with lower corrosion current density and higher corrosion potential and pitting potential (as shown in Table 3); in addition, the surface morphology after electrochemical corrosion (as shown in Table 3) Figure 6 There is no obvious corrosion phenomenon and no pitting pits on the surfaces of the three alloys.
[0051] These experimental results prove that this high-strength and corrosion-resistant dual-phase medium-entropy alloy has excellent corrosion resistance in corrosive environments and is suitable for application scenarios with high requirements on material corrosion resistance.
Claims
1. A high-strength, corrosion-resistant dual-phase medium-entropy alloy, characterized in that: The alloy is composed of the following elements in percentage by mass composition: Co: 27%-31%, Cr: 28%-32%, Ni: 27%-28%, Al: 1%-2.5%, Ti: 2%-4.5%, Cu: 5%-8%, Nb: 1%-1.5%, B<0.01%, Mg<0.02%, and the rest are inevitable impurities; the content ratio of L12 phase and FCC phase in the structure of the alloy is close to 1:2; by adding low-content Al, Ti, Cu, Nb elements and trace B and Mg grain boundary strengthening elements, the configuration entropy of the alloy reaches 1.49R, and no other brittle intermetallic compound second phase is precipitated in the structure; the pitting corrosion resistance of the alloy is greater than 30, and the corrosion current density in NaCl solution is less than 2×10 -7 A / cm 2 .
2. The method for preparing a high-strength, corrosion-resistant dual-phase medium-entropy alloy according to claim 1, characterized in that: The following steps are involved: Prepare each element according to a set mass percentage, and use a vacuum arc furnace to melt to obtain an alloy melt; Then, the alloy melt is subjected to a specific heat treatment, wherein the specific heat treatment includes a solution treatment at 1150° C. for 12 to 24 hours, followed by an aging treatment at a temperature range of 700 to 780° C. for 1 to 50 hours, and finally water-cooling to room temperature to obtain an alloy; The specific heat treatment can adjust the ratio of the L12 phase and the FCC phase in the alloy structure to be close to 1:2, thereby achieving a good match between strength and toughness.
3. The method for preparing a high-strength, corrosion-resistant dual-phase medium-entropy alloy according to claim 2, characterized in that: After the alloy is subjected to specific heat treatment, the alloy has a yield strength greater than 1 GPa, a tensile strength greater than 1.4 GPa, and an elongation greater than 15%.
4. The method for preparing a high-strength, corrosion-resistant dual-phase medium-entropy alloy according to claim 2, characterized in that: The heat treatment is carried out in a common box furnace or a vacuum heat treatment furnace.
Citation Information
Patent Citations
Precipitation strengthening high-entropy alloy component design and preparation method based on diffusion multi-section technology
CN114438391A
High-toughness heterogeneous multiphase core-shell structure medium-entropy alloy and preparation method thereof
CN115198162A
High-strength long-life high-entropy-hitting high-temperature alloy as well as preparation method and application thereof
CN116463526A